Replacement of L-amino acids by D-amino acids in the antimicrobial peptide ranalexin and its consequences for antimicrobial activity and biodistribution - Domhan, Cornelius; Uhl, Philipp; Kleist, Christian; Zimmermann, Stefan; Umstätter, Florian; Leotta, Karin; Mier, Walter; Wink, Michael (Molecules, 2019)
Infections caused by multidrug-resistant bacteria are a global emerging problem. New antibiotics that rely on innovative modes of action are urgently needed. Ranalexin is a potent antimicrobial peptide (AMP) produced in the skin of the American bullfrog Rana catesbeiana. Despite strong antimicrobial activity against Gram-positive bacteria, ranalexin shows disadvantages such as poor pharmacokinetics. To tackle these problems, a ranalexin derivative consisting exclusively of d-amino acids (named danalexin) was synthesized and compared to the original ranalexin for its antimicrobial potential and its biodistribution properties in a rat model. Danalexin showed improved biodistribution with an extended retention in the organisms of Wistar rats when compared to ranalexin. While ranalexin is rapidly cleared from the body, danalexin is retained primarily in the kidneys. Remarkably, both peptides showed strong antimicrobial activity against Gram-positive bacteria and Gram-negative bacteria of the genus Acinetobacter with minimum inhibitory concentrations (MICs) between 4 and 16 mg/L (1.9–7.6 µM). Moreover, both peptides showed lower antimicrobial activities with MICs ≥32 mg/L (≥15.2 µM) against further Gram-negative bacteria. The preservation of antimicrobial activity proves that the configuration of the amino acids does not affect the anticipated mechanism of action, namely pore formation.